MSK1 regulates transcriptional induction of Arc/Arg3.1 in response to neurotrophins. Issue 6 (11th May 2017) - Hunter, Chris J.; Remenyi, Judit; Correa, Sonia A.; Privitera, Lucia; Reyskens, Kathleen M. S. E.; Martin, Kirsty J.; Toth, Rachel; Frenguelli, Bruno G.; Arthur, J. Simon C.
Abstract : The immediate early gene activity‐regulated cytoskeletal protein (Arc)/Arg3.1 and the neurotrophin brain‐derived neurotrophic factor (BDNF) play important roles in synaptic plasticity and learning and memory in the mammalian brain. However, the mechanisms by which BDNF regulates the expression of Arc/Arg3.1 are unclear. In this study, we show that BDNF acts via the ERK1/2 pathway to activate the nuclear kinase mitogen‐ and stress‐activated protein kinase 1 (MSK1). MSK1 then induces Arc/Arg3.1 expression via the phosphorylation of histone H3 at the Arc/Arg3.1 promoter. MSK1 can also phosphorylate the transcription factor cyclic‐AMP response element‐binding protein (CREB) on Ser133. However, this is not required for BDNF‐induced Arc.Arg3.1 transcription as a Ser133Ala knockin mutation had no effect on Arc/Arg3.1 induction. In parallel, ERK1/2 directly activates Arc/Arg3.1 mRNA transcription via at least one serum response element on the promoter, which bind a complex of the Serum Response Factor (SRF) and a Ternary Complex Factor (TCF). Abstract : Activity‐regulated cytoskeletal protein (Arc/Arg3.1) is an immediate early gene involved in synaptic plasticity. In response to BDNF, we find that the kinase mitogen‐ and stress‐activated protein kinase 1(MSK1) promotes Arc/Arg3.1 mRNA induction in primary cortical neuronal cultures. Although MSK1 is capable of phosphorylating the transcription factor cyclic‐AMP response element‐binding protein (CREB) on Ser133, it appears to regulate Arc/Arg3.1, at least in part, via the phosphorylation of histone H3 at the Arc/Arg3.1 promoter.